Subtype prediction of primary aldosteronism by combining aldosterone concentrations in the left adrenal vein and inferior vena cava: a multicenter collaborative study on adrenal venous sampling. (January 2018) - Fujii, Yuichi; Umakoshi, Hironobu; Wada, Norio; Ichijo, Takamasa; Kamemura, Kohei; Matsuda, Yuichi; Kai, Tatsuya; Fukuoka, Tomikazu; Sakamoto, Ryuichi; Ogo, Atsushi; Suzuki, Tomoko; Nanba, Kazutaka; et al.
Abstract Subtype diagnosis of primary aldosteronism (PA) by adrenal vein sampling (AVS) is recommended as a mandatory step for indicating adrenal surgery. It is a technically demanding procedure, especially in the right adrenal vein. The aim of the study was to predict the subtype diagnosis in the absence of values from the right AVS. From the databases of nine centers (WAVES-J), 308 patients with PA who underwent successful AVS were studied. Based on the ipsilateral ratio (IR) (aldosterone/cortisol ratio of the left adrenal vein [A/Cleft AV ] / aldosterone/cortisol ratio of the inferior vena cava [A/CIVC ]), the patients were divided into two groups: the patients with IR ≥ 1.0 (n = 262) and those with IR < 1.0 (n = 46). In patients with IR > 1.0, the A/Cleft AV was significantly higher in patients with the left unilateral subtype than in patients with the bilateral subtype. Receiver operating characteristic (ROC) curve analysis revealed that an A/Cleft AV cutoff >68 showed 70.8% sensitivity and 93.5% specificity for the left unilateral subtype. On the other hand, in patients with IR < 1.0, the A/Cleft AV was significantly lower in patients with the right unilateral subtype. ROC analysis revealed that an A/Cleft AV cutoff <9 showed 86.7% sensitivity and 75.0% specificity for the right unilateral subtype. Hence, the combination of the IR and A/C ratio in the left adrenal vein is useful for predicting the subtype. The present results provide important information for patients with PA in whom AVS was unsuccessful in the right adrenal vein.